Organizational Climate in State MTs in Bandar Lampung - Erminda, Ridwan; Ranosa, M. Risky (Journal of Advanced Islamic Educational Management, 2024)
This study aims to evaluate the organizational climate in Madrasah Tsanawiyah Negeri Bandar Lampung City that affects performance. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results showed that the madrasah climate fulfills the aspects of physical security, social-emotional, learning activities, and relationships between school members. However, aspects of the institutional environment, especially related to cleanliness, facilities, and spatial layout, still require improvement. Efforts to improve these aspects are important to create an optimal work climate and support performance.